Methodology and applications for integrating earthquake aftershock risk into performance-based seismic design - Nazari Khanmiri, Negari, author; van de Lindt, John, advisor; Heyliger, Paul, committee member; Mahmoud, Hussam, committee member; Senior, Bolivar, committee member (Colorado State University. Libraries, 2015)
Aftershocks have the potential to cause severe damage to buildings and contribute to threaten life safety following a major earthquake. However, their effect on seismic hazard is not explicitly accounted for in modern building design codes, nor in emerging methodologies such as performance-based seismic design. In this dissertation a methodology was developed to systematically integrate aftershock seismic hazard into performance-based earthquake engineering (PBEE). This is achieved through a combination of analytical studies with structural degradation models derived from existing publicly available Network for Earthquake Engineering Simulation (NEES) data as well as numerical models. The design adjustments due to aftershock seismic hazard were calculated for the Direct Displacement Design (DDD) approach for a building portfolio. A comprehensive sensitivity analysis was performed to investigate the effect of different factors such as the location and number of stories of the building and magnitudes of mainshocks and aftershocks on the design adjustments needed. The results of this research will have multiple applications such as allowing code developers to investigate different options for change in structural design to account for aftershock hazard. Aftershock consideration can be an option for stake holders in selection of their design criteria to minimize life-cycle cost. Since aftershock hazard is a major consideration when safety tagging a building following an earthquake, the results of this project will provide insight into quantitatively investigating risk for damaged buildings.
Keywords: collapse fragility; performance-based seismic design; woodframe building; hysteretic parameters; aftershock hazard; total collapse probability